PERTANGGUNGJAWABAN LEMBAGA PERBANKAN TERHADAP PENCURIAN DATA NASABAH - Lukmanul Hakim (Dialogia Iuridica, 2018)
Cyber crime or cyber crime is basically an impact of technological developments that have changed the habit of the community that was originally conventional into a more modern habits or can be called a high technology society. This change of habit has resulted in a crime with the use of electronic devices as a crime medium. The main factor that resulted in the switching of these habits is the development of information technology combined with communication media and computer technology, which then produces a new device called Internet. The emergence of the Internet has resulted in a new interaction pattern in the life of society, which initially more real (real) changed into patterns of interaction masayakat which can be said to be virtualÂ Keywords: Bank, Data Theft, Cyber.PERTANGGUNGJAWABAN LEMBAGA PERBANKAN TERHADAP PENCURIAN DATA NASABAH